NCOG-19. BEVACIZUMAB IN REAL LIFE PATIENTS WITH RECURRENT GLIOBLASTOMA: BENEFIT OR FUTILITY?. (9th November 2020) - Smolenschi, Cristina; Colomba, Emeline; Rassy, Elie; Lezghed, Naima; Kettab, Mohamed; Louvel, Guillaume; Garcia, Gabriel; Cheaib, Bianca; Bockel, Sophie; Pallud, Johan; Dezamis, Edouard; Copaciu, Razvan; et al.
Abstract: Angiogenesis represents a hallmark of glioblastoma but most trials disappointed and failed to change the poor outcome of this disease. However, Bevacizumab (Bev) is widely used in clinical practice by expert oncologists due to experience or efficacy in real life.We retrospectively reviewed the use of Bev and its benefit in terms of Time to treatment failure (TTF), Overall Survival(OS), Objective Response Rate (ORR) and clinical benefit. METHODS: We analyzed two hundred and two patients treated at Gustave Roussy Cancer Campus with Bev until definitive failure for recurrent glioblastoma between 2006 and 2016. Patients were treated with Bev alone or in association with radiotherapy, temozolomide, lomustine or irinotecan. RESULTS: The median duration of Bev treatment until definitive failure was 6 months. The median TTF was 7.27 months(95%CI 6.30-8.24) and the median OS from diagnosis was 22.43 months(95%CI 19.68-25.18). Two patients were still alive without active treatment at the end of study. A hundred and fourteen (56%) patients experienced symptom amelioration and seventy-five (37%) improved their Performance Status. Fifty percent of patients exhibited Partial and Complete Response on MRI, as best radiological response, within 1.6 months. No patient had anaphylactic reaction. Grade 1-2 hypertension(HT)(17%) and grade 1(10%) proteinuria were most common. Six patients presented lethal toxicity: 4 with GI perforation, 1 p with cerebral hemorrhage and 1 p with arterial bleeding. HT was correlated with treatment response in 67% of patients. A neutrophil count superior to 6000/mm³ was associated with longer TTF(mTTF 8.23m(95%CI 6.64-9.82). CONCLUSION: This retrospective study reports a substantial clinical benefit of Bev in patients with recurrent glioblastoma with an acceptable toxicity profile. As the panel of therapeutic option is still very limited in these tumors, this work supports the maintained use of Bev as a therapeutic option.